ANALYSIS OF STOCHASTIC RELIABILITY AND FAILURE RISK OF COLUMN DISCONNECTOR UNDER TYPHOON BASED ON THE PROBABILITY DENSITY EVOLUTION MODEL - SHI ShouJian; CHEN WenTong; YANG HuanHong; ZHU LiangLong; WU XueFeng; XU ChengHao (Jixie qiangdu)
To estimate the structural failure risk of column disconnector subjected to typhoon, the efficient solution model of stochastic reliability was established considering the uncertainties of wind field and material resistance. First, the typhoon random field model was given based on the power spectral density, in which the uncertainties of ground roughness, average wind speed, and boundary wave number were incorporated. Then, the three-dimensional structural mechanies analysis model of disconnector was proposed based on the Abaqus software. Third, the calculation method of probability density function of structure target variable was obtained using the probability density evolution model (PDЕM). Finally, the efficient solution strategy was realized by the joint simulation of Matlab and Abaqus. Results indicated that the extreme stress of the bottom section of insulating pillar was the mainly dominated parameter. The uncertainties of wind field and material resistance have great influence on fragility curve. The uncertainty of material aspect should be controlled in structure design.